Biodegradation and power production kinetics in microbial fuel cell during rice mill wastewater treatment. (1st May 2023) - Raychaudhuri, Aryama; Behera, Manaswini
Graphical abstract: Highlights: Effect of COD and lignin concentration on electricity generation in MFC. A maximum power density of 4.3 W/m 3 was obtained with COD concentration of 2.5 g/L. Han–Levenspiel model was found suitable for kinetic parameter estimation. Lignin degradation capacity of 0.063 ± 0.007 kg/m 3 ∙d was obtained. Exoelectrogens can tolerate high concentrations of lignin in wastewater. Abstract: The influence of the initial substrate concentration of rice mill wastewater on substrate degradation rate and power production in a dual-chambered MFC was explored over a wide range of chemical oxygen demand (COD: 500–6000 mg/L) and lignin (77.5–930 mg/L) levels. Within a limited concentration range, increasing COD concentration increased degradation rates and electricity generation, but both processes were hindered at high substrate concentrations. A maximum power density of 4.3 W/m 3 was attained in a MFC operated with an initial COD concentration of 2480 ± 17 mg/L which can be attributed to the low ohmic resistance (23.8 Ω) due to better solution conductivity. Different kinetic models were used to examine inhibition kinetics from an electrical perspective. The relationship between power density and COD concentration was best described by Han–Levenspiel model. The maximum power density, half-saturation constant, and critical inhibitory concentration were predicted to be 4.56 W/m 3, 799.6 mg/L, and 7627 mg/L, respectively. A maximum lignin degradation rate of 0.063 ± 0.007 kg/m 3 ∙d was achieved at a lignin concentration of 387.5 ± 2.8 mg/L which accounts for 83.17 ± 0.26 % removal efficiency, suggesting the possibility of lignin degradation in MFC even at higher concentrations. The detection of low molecular weight degradation by-products of lignin in the effluent sample further confirmed the ability of exoelectrogens to degrade lignin.